Gambaran Fatigue Pada Pasien Kanker Payudara Di Rumah Sakit Kanker Dharmais Menggunakan Instrumen Esas (Edmonton Symptom Assesment System) - Heni Nurhaeni Heni; Achmad Fauji; Hani Fauziah (FKF, 2024)
Background: Breast cancer is one of the most common types of cancer suffered by women in Indonesia. One of the effects of breast cancer is fatigue or exhaustion. Fatigue is caused due to the effects of the cancer treatment process. Fatigue can be measured or assessed using the ESAS (Edmonton Symptom Assessment System) instrument. Purpose: This study aims to determine the characteristics of the respondents and the description of fatigue in breast cancer patients at the Dharmais Cancer Hospital using the ESAS (Edmonton Symptom Assessment System) instrument Methods: This study used a quantitative descriptive method with a cross-sectional approach. The population in this study were breast cancer patients at the Dharmais Cancer Hospital. The sampling technique used accidental sampling technique with a total of 100 respondents. Results: The results of this study showed that breast cancer respondents had no symptoms of fatigue 8 (8%) respondents, mild fatigue 33 (33%) respondents, moderate fatigue 56 (56%) respondents and severe fatigue 3 (3%) respondents. Conclusion: This study can be concluded that fatigue or exhaustion due to the process of breast cancer treatment from 100 respondents was obtained at a moderate level of fatigue, namely as many as 56 (56%) respondents.